PENGARUH PEMUPUKAN NPK MAJEMUK DAN UREA TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO - Hasmi, Idrus; Zarwazi, L. M.; Widyantoro, Widyantoro; Ruskandar, A. (Agroswagati : Jurnal Agronomi, 2020)
Research on improving fertilization technology of upland rice is still being developed. This research aimed to examine the most efficient technology fertilization (NPK and Urea) to increase the productivity of upland rice. Research had been conducted in upland rice fields, located at Ploso Kerep, Indramayu District, in MT I 2012/2013 designed in split plot with three replications. The main plot was the level of NPK fertilizer, consisting of (A) Without NPK (0 kg / ha), (B) NPK 100 kg / ha, (C) NPK 200 kg / ha, and (D) NPK 300 kg / Ha, and as subplots are (1) Without Urea 0 kg / ha, (2) Urea 100 kg / ha, (3) Urea 200 kg / ha and (4) Urea 300 kg / ha. The results showed that NPK and Urea can improve growth and yield of upland rice. NPK fertilizer with 300 kg / ha has produced the highest number of panicles per hill (12.07 grain panicles), while at Urea 200 kg / ha resulted in the highest panicle number of 11.54 grain panicles. The highest dry grain yield (5.78 t / ha) was obtained at NPK 300 kg / ha with an average increase of 100 kg / ha NPK reaching 370 kg / ha. The combination of NPK 300 kg / ha and with 300 kg urea / ha, the weight of 1000 urea 300 kg / ha can be increased to 7.58% when compared without fertilizing.